2019
DOI: 10.12928/telkomnika.v17i5.11798
|View full text |Cite
|
Sign up to set email alerts
|

A temperature characterization of (Si-FinFET) based on channel oxide thickness

Abstract: This paper presents the temperature-gate oxide thickness characteristics of a fin field-effect transistor (FinFET) and discusses the possibility of using such a transistor as a temperature nano-sensor. The investigation of channel oxide thickness-based temperature characteristics is useful to optimized electrical and temperature characteristics of FinFET. Current-voltage characteristics with different temperatures and gate oxide thickness values (Tox=1, 2, 3, 4, and 5 nm) are initially simulated, and the diode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…The Si channel FinFET has the better electrical characteristics with working temperature as shown in FIGURE 12 [30]. According to the results, the temperature sensitivity of FinFET increases linearly with oxide thickness within the range of 1-5 nm, furthermore, the threshold voltage and drain-induced barrier lowering increase with increasing oxide thickness.…”
Section: Figure 3 22nm Tri-gate Transistor [21]mentioning
confidence: 91%
See 1 more Smart Citation
“…The Si channel FinFET has the better electrical characteristics with working temperature as shown in FIGURE 12 [30]. According to the results, the temperature sensitivity of FinFET increases linearly with oxide thickness within the range of 1-5 nm, furthermore, the threshold voltage and drain-induced barrier lowering increase with increasing oxide thickness.…”
Section: Figure 3 22nm Tri-gate Transistor [21]mentioning
confidence: 91%
“…Also it can concluded that the obtained results show that the SiGe FinFET is suitable for the analog application. Effects of working temperature on MOS structure and its electrical parameters has been studied and well expressed in many research papers [27][28][29][30], FinFET temperature characteristics has been investigated by [28,30], based on transfer characteristics of FinFET at drain voltage (Vd=1V) were investigated with different working temperature (-25, 0, 25, 50, 75, 100, and 125 o C) with Si, Ge, GaAs and InAs as a semiconductor channel. The final results indicate that the Ion/Ioff decreased (FIGURE 11) with increasing working temperature for all semiconductors channel types, but with best temperature stability with InAs and best temperature sensitivity with Si.…”
Section: Figure 3 22nm Tri-gate Transistor [21]mentioning
confidence: 99%
“…The transistor based temperature sensors are designed depending on the temperature characteristics of currentvoltage curves of the Nanowire transistor [21,22]. The bipolar transistor can be used as a temperature sensor by connecting the base and collector together.…”
Section: Related Workmentioning
confidence: 99%
“…However, reducing the size of conventional planar transistors would be exceptionally challenging due to electrostatic leakages and other fabrication issues [4], [5]. The application of nano-science and its inherent technology has been extensively used in interdisciplinary research, particularly in the past two decades [6], [7].…”
Section: Introductionmentioning
confidence: 99%